Sex differences in mate preferences: Testing some predictions from evolutionary theory - Tadinac, Meri (Array, 2004)
Hypotheses of evolutionary psychologists concerning the mate choice and sex differences in preferred mate characteristics have been tested in various cultures. In this paper some of the basic assumptions that can be drawn from famous Trivers' theory of parental investment and sexual selection are tested on a Croatian sample. The theory predicts sex differences when it comes to choosing a mate due to different parental investment in offspring. Females are expected to be choosier than males and to seek a reliable partner who has the resources and is willing to invest them in potential offspring (in order to increase their survival), while males should mostly seek a healthy and reproductively capable partner. The basic assumptions derived from the theory received empirical support: men seek short-term mates more than women do ; sex differences were found in rankings of desirability of certain characteristics of a potential mate, as well as in his/her preferred age ; more men than women would express sexual vs. emotional jealousy.